Análisis del discurso de campañas publicitarias producidas por la Universidad Nacional de Chimborazo en el 2019 y su correlación con el impacto en los segmentos de mercado - Silva Suárez, Cynthia Daniela (2022)
The research´s purpose is to evaluate the advertising environment around the Universidad Nacional de Chimborazo, carry out the analysis through different research methods, campaigns that have been carried out in the past, noting their strengths and weaknesses, based on this, correcting said errors and from this create an advertising communication manual, which will facilitate that in future advertising actions that are required, follow a regulation, combining different elements that come to fulfill their function in an optimal way, and that they are friendly with the users.